If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4v + 2(-1 + -6v) = -130 -4v + (-1 * 2 + -6v * 2) = -130 -4v + (-2 + -12v) = -130 Reorder the terms: -2 + -4v + -12v = -130 Combine like terms: -4v + -12v = -16v -2 + -16v = -130 Solving -2 + -16v = -130 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -16v = -130 + 2 Combine like terms: -2 + 2 = 0 0 + -16v = -130 + 2 -16v = -130 + 2 Combine like terms: -130 + 2 = -128 -16v = -128 Divide each side by '-16'. v = 8 Simplifying v = 8
| -2(2y-6)-y=-2(y-3) | | 2a-4=3(a-4) | | x^2+(1-i)x-1=0 | | 2(2y-1)=-19 | | -32+8v=6(v-7) | | 2b^2+3b-2= | | -42=3(6+8b)+6(-3b-7) | | 9x-2=133 | | 60=-5(6n-6) | | 38-n=5+4(-2n+3) | | -26+6p=-8(1-3p) | | 2(r+4)=-35 | | 580=-20b | | 9y+12=84 | | 21x-3=40x | | 2(3-x)=60 | | -5.5=-3.4 | | 7(x-2)=5(x-4) | | -7(7n+7)=39-5n | | 3+r=19 | | 10b^2-15b-8b+12b=0 | | 12x^4+10x^3-12x^2=0 | | -3n-2(-8n-3)=-14+3n | | 6x+12+54=180 | | 18x+6=19x | | 2(2p-3)=36-2p | | 8(8x-1)+4(1+8x)=-4 | | -23=6x+2 | | 16x^2-72x+75=0 | | 9x+6=-36 | | 32=-6x+2 | | 69-1=9+20 |